Pengaruh Kebijakan Deviden, Sustainability Reporting, dan Arus Kas Pendanaan terhadap Return Saham Dimoderasi Nilai Perusahaan - Iska Ayu Sundari; Nera Marinda Machdar (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The business world is getting tougher due to the large number of new companies. Company management must compete and overcome difficulties. Shareholders need to evaluate the company's prospects in the future. The stock return received by shareholders is one of the important factors that help investors assess the company's prospects. The purpose of this study is to analyze and review the effect of dividend policy, sustainability reporting, funding cash flow on stock returns moderated by firm value. This research method uses descriptive qualitative. By describing the data obtained from literature review, a phenomenon can be studied. These data can provide new insights into the phenomenon and identify problems that remain unanswered. The results of this study indicate that the variables of dividend policy, sustainability reporting, and funding cash flow affect stock returns. And company value can moderate dividend policy, sustainability reporting, and funding cash flow on stock returns.